Livestock manure as an alternative attractant for fruit flies (Diptera: Tephritidae) in guava tree - Rosenya Michely Cintra Filgueiras; Francisco Roberto de Azevedo; Raul Azevedo; Ricardo Braga de Farias; Cristiane Ramos Coutinho (Pesquisa Agropecuária Tropical, 2016)
Fruit flies are typically managed using hydrolyzed protein, which is difficult for family farmers to obtain. This study aimed at assessing the efficiency of livestock manure for monitoring and/or controlling this pest in guava tree orchards. The first experiment tested the efficiency of guava juice and manure from cattle, sheep, pig, horse and chicken as attractants for fruit flies. Once the best bait had been established, a second experiment was conducted using guava juice and chicken manure extract at concentrations of 10 %, 30 %, 50 %, 70 % and 100 %. A third assay analyzed guava juice and chicken manure extract (10 %) at three attractant aging periods (3, 7 and 14 days after trap installation). The cost-effectiveness ratio between guava juice and extract was also analyzed. It was concluded that fruit flies prefer the chicken manure extract (10 %), with greater capture observed three days after trap installation, which can replace the guava juice in the agroecological management of fruit flies in guava trees in family farms, since it is low cost and efficient.